The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.56899/150.05.06
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and Dynamics Simulations Study of Selected Phytoconstituents of “Pangi” (Pangium edule Reinw) Leaf as Anti-SARS-CoV-2

Abstract: Herbal plants are often used as alternative medicine because they contain active compounds for the treatment of diseases and disorders with minimal side effects, and are easily obtained from the surrounding environment. Some of them have antiviral activity. This study aimed to analyze the potential of phytochemical compounds in the leaf of “pangi” (Pangium edule Reinw) as antiSARS-CoV-2 using molecular docking study. The drug- and lead-likeness properties of the selected compounds were obtained from the Swiss … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The main product of this plant is the endosperm of its fruit seed which is usually consumed as a spice or an added ingredient to several local dishes. However, its consumption is compromised by its relatively high amount of cyanogen, making it poisonous and unsafe to eat (Deshpande et al 2000;Sailah et al 2021). Cyanogen is an antinutrient that limits the optimum utilization of plant food sources because of its adverse effects on human health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main product of this plant is the endosperm of its fruit seed which is usually consumed as a spice or an added ingredient to several local dishes. However, its consumption is compromised by its relatively high amount of cyanogen, making it poisonous and unsafe to eat (Deshpande et al 2000;Sailah et al 2021). Cyanogen is an antinutrient that limits the optimum utilization of plant food sources because of its adverse effects on human health.…”
Section: Introductionmentioning
confidence: 99%
“…This can provide the chemical basis as to how Pangi seeds become edible and safe for consumption after processing. Although review of literature does not reveal records on food poisoning cases from Pangi seeds in the Philippine setting, there are references stating that fresh Pangi fruit and seeds are high in hydrogen cyanide which is a deadly poison (Deshpande et al 2000;Etoh 2001;Sailah et al 2021). Furthermore, interviews with the Obu Manuvu community revealed that consuming unprocessed Pangi seeds results in poisoning for both humans and animals.…”
Section: Introductionmentioning
confidence: 99%